Effectiveness of kinesiotaping on diaphragm thickness, diaphragmatic thickening fraction, and intercostal muscle thickness in patients undergoing mechanical ventilation: a pilot study - Metin Ökmen, Burcu; Ökmen, Korgün (The European Research Journal, 2019)
Objective: We aimed to evaluate the effects of kinesiotaping applied on the chest wall on the diaphragmatic muscle and intercostal muscles in patients receiving mechanical ventilation. Methods: In this prospective, randomized, controlled, double-blind study, 24 patients who underwent mechanical ventilation in the intensive care unit were included the study. Randomization was used to identify the side of patients that the kinesiotaping was applied to. Group 1: side that kinesiotaping was applied (n = 24) and Group 2 (control group): side that kinesiotaping was not applied (n = 24). Kinesiotaping was changed in every 3 day. Thicknesses of diaphragmatic muscle, seventh intercostal muscle and ninth intercostal muscle were evaluated by using ultrasound in pretreatment, third day, sixth day and ninth day. Results: In both groups; a statistically significant decrease was found in all the evaluation parameters at all the measurement times when compared to the pretreatment values (p < 0.05). On the third day and sixth day; a statistically significant difference was found in favor of group 1 in all the evaluation parameters except thickness of seventh intercostal muscle (p < 0.05). On the ninth day; there was no statistically significant difference between the two groups (p > 0.05). Conclusion: In conclusion, our study results showed that kinesiotaping decelerated the decrease in the diaphragmatic muscle and the intercostal muscles thickness until sixth day.